2018
DOI: 10.3847/1538-4357/aaad12
|View full text |Cite
|
Sign up to set email alerts
|

Testing Viable f(T) Models with Current Observations

Abstract: We perform observational tests on the f(T) gravity with the BAO data (including the BOSS DR 12 galaxy sample, the DR12 Lyα-Forests measurement, the new eBOSS DR14 quasar sample, the 6dFGS, and the SDSS), the CMB distance priors from the Planck 2015, the SNIa data from the joint light-curve analysis, the latest H(z) data, and the local value of the Hubble constant. Six different f(T) models are investigated. Furthermore, the ΛCDM is also considered. All models are compared by using the Akaike information criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 92 publications
23
50
0
Order By: Relevance
“…Lastly, our constraints for f 1 CDM and f 2 CDM models are in very good agreement with those of and Xu et al [65] who combined SNIa/H(z)BAO/CMB shi f t data. Concerning f 3 CDM model our best fit value for b is somewhat lower with that of [65]. Specifically, these authors found: Finally, in order to give the reader the opportunity to appreciate the new results of our study we conclude this section with a brief discussion regarding our new and novel statistical results.…”
Section: Fitting F (T ) Models With H(z) Datasupporting
confidence: 90%
See 1 more Smart Citation
“…Lastly, our constraints for f 1 CDM and f 2 CDM models are in very good agreement with those of and Xu et al [65] who combined SNIa/H(z)BAO/CMB shi f t data. Concerning f 3 CDM model our best fit value for b is somewhat lower with that of [65]. Specifically, these authors found: Finally, in order to give the reader the opportunity to appreciate the new results of our study we conclude this section with a brief discussion regarding our new and novel statistical results.…”
Section: Fitting F (T ) Models With H(z) Datasupporting
confidence: 90%
“…Specifically, these authors found: Finally, in order to give the reader the opportunity to appreciate the new results of our study we conclude this section with a brief discussion regarding our new and novel statistical results. Although, our observational constraints are in qualitative agreement with previous studies on f (T ) gravity [56][57][58][59][60][62][63][64][65], we would like to spell out clearly the reasons of which our analysis improves the observational constraints of f (T ) models with respect to previous studies. Firstly, we include for the first time the covariance matrix of H(z) data in f (T ) models, and we utilize at the same time the recently proposed statistical method of [68], which is not affected by the Hubble constant problem.…”
Section: Fitting F (T ) Models With H(z) Datasupporting
confidence: 89%
“…Thanks to the nice feature of the f (T ) theory being its field equations second order; currently there are viable f (T ) theories of gravity which give good results with a wide range of cosmological observations Nunes et al (2016); Xu et al (2018); Nunes (2018). In the following sections, we focus on a specific model with IR torsional gravity which is in principle an alternative to phantom dark energy.…”
Section: F (T ) Cosmologymentioning
confidence: 99%
“…One may use cosmological observations of the background level to extract the constraints on the model parameter p [71][72][73][74][75]. However, in the present work we are interested in examining whether it is possible to constrain p using the post-Newtonian observations and the perturbation analysis of the previous section.…”
Section: The Power-law Modelmentioning
confidence: 99%